1992
DOI: 10.1007/bf02245170
|View full text |Cite
|
Sign up to set email alerts
|

Abolition of latent inhibition by a single 5 mg dose ofd-amphetamine in man

Abstract: The performance of healthy volunteer subjects on an auditory latent inhibition (LI) paradigm was assessed following administration of a single oral dose of d-amphetamine or placebo. It was predicted that a low (5 mg), but not a high (10 mg), dose of d-amphetamine would disrupt LI. The prediction was supported with left ear presentation of the preexposed stimulus only. When the preexposed stimulus was presented to the right ear the predicted pattern of findings was not obtained. It is concluded that the dopamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
85
5
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(108 citation statements)
references
References 26 publications
17
85
5
1
Order By: Relevance
“…It has been repeatedly reported that systemic application of amphetamine disrupts latent inhibition in hum ans (Gray et al 1992) as well as in rats (Solomon et al, 1981;Weiner et al 1981;Killcross et al 1994), using a variety of different learning paradigms, There is, however, m uch m ore controversy regarding the individual dopam inergic terminal fields. Thus, Solomon and Station (1982), using a conditioned avoidance approach, have reported a reduction in latent inhibition after local application of dopam ine into the nucleus accum bens, whereas similar injections into the dorsal striatum had no effect (cf.…”
Section: Introductionmentioning
confidence: 44%
“…It has been repeatedly reported that systemic application of amphetamine disrupts latent inhibition in hum ans (Gray et al 1992) as well as in rats (Solomon et al, 1981;Weiner et al 1981;Killcross et al 1994), using a variety of different learning paradigms, There is, however, m uch m ore controversy regarding the individual dopam inergic terminal fields. Thus, Solomon and Station (1982), using a conditioned avoidance approach, have reported a reduction in latent inhibition after local application of dopam ine into the nucleus accum bens, whereas similar injections into the dorsal striatum had no effect (cf.…”
Section: Introductionmentioning
confidence: 44%
“…Based on this pharmacological connection, LI-disruption was suggested as a potential model of the selective attention deficit found in schizophrenia. Subsequently, LI has been found to be disrupted in acute psychotic schizophrenic patients (Baruch et al, 1988), and in normal humans treated with amphetamine (Gray et al, 1992). These and other evidence support the validity of LI-disruption as a model of processing deficits in acute schizophrenia.…”
Section: Generalizing the Model To LI Disruption Introductionmentioning
confidence: 69%
“…Consistent with the widely documented difficulty to ignore irrelevant stimuli in schizophrenia, LI is disrupted in some subsets of schizophrenic patients (Baruch et al 1988;Dunn and Scibilia 1996;Gray et al 1992aGray et al , 1995Vaitl and Lipp 1997; but see Swerdlow et al 1996b;Williams et al 1998), and this disruption is modeled by loss of LI in amphetamine-treated rats (Killcross et al 1994a;Solomon et al 1981;Weiner et al 1981Weiner et al , 1984Weiner et al , 1988 and in normal humans (Gray et al 1992b; Thornton et al 1996). The validity of the model is further strengthened by findings that the neural substrates of LI in the rat include the hippocampal formation and the nucleus accumbens, consistent with the temporal lobe and mesolimbic pathology implicated in the pathophysiology of schizophrenia (for review, see Weiner 1990;.…”
mentioning
confidence: 72%